Microdermabrasion facilitates direct current stimulation by lowering skin resistance - P. Y. Chhatbar; S. Liu; V. Ramakrishnan; M. S. George; S. A. Kautz; W. Feng (Wiley, 2022)
Abstract Background Transcranial direct current stimulation (tDCS) is reported to induce irritating skin sensations and occasional skin injuries, which limits the applied tDCS dose. Additionally, tDCS hardware safety profile prevents high current delivery when skin resistance is high. Objective To test if decreasing skin resistance can enable high‐dose tDCS delivery without increasing tDCS‐related skin sensations or device hardware limits. Methods We compared the effect of microdermabrasion and sonication on 2 mA direct current stimulation (DCS) through forearm skin for 2-3 min on 20 subjects. We also surveyed the subjects using a questionnaire throughout the procedure. We used a linear mixed‐effects model for repeated‐measures and multiple logistic regression, with adjustments for age, race, gender and visit. Results Microdermabrasion, with/out sonication, led to significant decrease in skin resistance (1.6 ± 0.1 kΩ or ∼32% decrease, p < 0.0001). The decrease with sonication alone (0.4 ± 0.1 kΩ or ∼7% decrease, p = 0.0016) was comparable to that of sham (0.3 ± 0.1 kΩ or ∼5% decrease, p = 0.0414). There was no increase in the skin-electrode interface temperature. The perceived DCS‐related sensations did not differ across skin preparation procedures (p > 0.16), but microdermabrasion (when not combined with sonication) led to increased perceived sensation (p < 0.01). Conclusions Microdermabrasion (with/out sonication) resulted in reduced skin resistance without increase in perceived skin sensations with DCS. Higher current can be delivered with microdermabrasion‐pre‐treated skin without changing the device hardware while reducing, otherwise higher voltage required to deliver the same amount of current.